The relationship between CEO characteristics and banks' risk-taking: Review and research directions - Patrick Hertrampf; Thomas M. Brunner-Kirchmair; Martin R. W. Hiebl; Arnd Wiedemann (Schmalenbach Journal of Business Research (SBUR), 2025)
The fundamental role of the banking sector in society and the economy necessitates extensive regulation and supervision. Given that increased risk-taking behavior can undermine the stability of the banking sector, it is crucial to identify the factors affecting banks' risk-taking. This study focuses on the impact of chief executive officer (CEO) characteristics on banks' risk-taking behavior. To achieve this, we conduct a~systematic literature review and analyze the findings through the lens of the upper echelons theory (UET) framework. Our analysis reveals that banks' risk-taking is measured in diverse and often arbitrary ways, highlighting the need for standardized measurement methods to ensure comparability. Our findings also indicate that various CEO characteristics, including demographic, psychological, social psychological, biological, and other traits, significantly influence banks' risk-taking. These results suggest that stringent regulations do not serve as a~boundary condition for UET. We propose five research avenues, include new methods for measuring CEO characteristics (such as linguistic approaches), explore new areas of research based on the developments of UET (such as moderators and the objective situation), refine the measurement of banks' risk-taking, address questions regarding control variables, and identify additional CEO characteristics of major interest (such as emotional intelligence or CEO attractiveness). Our study underscores the relevance of UET in banking, providing valuable insights for practitioners, academics, and regulators.
Keywords: D81; D91; G01; G21; G41; 650; Bank; Executives; Risk-taking; Upper echelons